Investigation of pore structure and petrophysical property in tight sandstones. (March 2018) - Lai, Jin; Wang, Guiwen; Cao, Juntao; Xiao, Chengwen; Wang, Song; Pang, Xiaojiao; Dai, Quanqi; He, Zhibo; Fan, Xuqiang; Yang, Liu; Qin, Ziqiang
Abstract: Laboratory measurements include porosity, permeability, high pressure mercury intrusion (HPMI), nuclear magnetic resonance (NMR) measurements and microscopic analysis of thin sections and scanning electron microscope (SEM) were used to gain insight into the nature of the pore throat structure including pore geometry, pore size distribution and pore connectivity of Bashijiqike tight gas sandstones in Keshen 5, Keshen 6, Keshen 8, Keshen 9 and Keshen 13 Wellblock of Kuqa depression. The relationships between microscopic pore structure parameters and macroscopic petrophysical behaviors were investigated by regression analysis. The results show that various types of pores with wide ranges of pore radius are observed. The pore throats are very small (commonly <1 μm), and large pores are generally connected by tiny pore throats. Pore throats larger than r apex (pore radius at the apex of the Pittman's hyperbola) accounts for a small fraction of the pore volume, but make a significant contribution to permeability. The porosity connected by large pore throats (> r apex ) controls permeability in tight gas sandstones. The NMR pore size distribution is broader than the HPMI pore throat distribution. In the NMR analysis, only the pore systems connected by the relatively large pore throats should be accounted as movable, and some portion of large pores, which are not connected by effective large pore throats, are not effectively movable. The effective movable porosity is calculated by excluding those pores restricted by the tiny pore throats. The content of effective movable porosity from NMR measurements shows good correlation relationship with the porosity connected by large pore throats in HPMI analysis. Three typical types of pore structures are recognized through thin section, SEM analysis combined with the capillary curve and NMR T2 spectrum, and the microscopic and macroscopic characteristics of the three pore structures are investigated. The pore structure were comprehensively evaluated and characterized by linking NMR T2 spectrum with HPMI analysis. Highlights: Microscopic pore structure and petrophysical property in tight sandstones is investigated. Large pore throats make a significant contribution to permeability. Pores connected by large pore throats are accounted as movable in NMR analysis.